Actualization of approaches to development design under conditions of digital transformation of the socio-economic environment - Malykhin , M. (Ways to Improve Construction Efficiency, 2022)
This work explores contemporary transformational processes that influence the field of development design amid the digitalization of the socio-economic environment. Special attention is given to the rethinking of traditional approaches to the initiation, planning, and implementation of development projects, taking into account changes in consumer behavior, the growing role of data, the necessity for sustainability, and the need for rapid adaptation to new contexts. A systemic approach is proposed for updating development strategies, considering the influence of intelligent platforms, analytical tools, and modeling technologies (BIM, GIS, digital twins) at all stages of the project cycle. It is determined that a key objective is to build an adaptive digital ecosystem in which management decisions are made based on real-time data, and risks are anticipated through scenario modeling. The need for a transition to the concept of dynamic project management is justified, where planning is not separated from execution but occurs within an interactive environment with constant goal and priority updates. The study examines the new roles of the developer as a coordinator of digital flows and an integrator of social, economic, and technological changes—no longer simply an investor or client. This requires a rethinking of competencies within development structures, which must combine analytical, design, and managerial skills within a unified digital space. Special attention is devoted to changes in approaches to forming urban concepts, designing functionally mixed environments, assessing environmental neutrality, and analyzing an object’s life cycle. A methodological framework is proposed for the digital reconfiguration of development models, considering sustainability factors, stakeholder involvement, and urban evolution. Conceptual principles are also formulated for building a new paradigm of development design—based on flexibility, dynamism, integration with digital services, and the management of information flows.